2016
DOI: 10.1055/s-0041-110449
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Variability in the Differential Diagnosis of Benign Bone Tumors and Tumor-like Lesions

Abstract: Purpose: The interobserver-variability of radiological diagnosis of benign bone tumors (BBT) and tumor-like lesions (TLL) was examined in order to identify difficult-to-diagnose entities, to examine the frequency of advanced diagnostics and to describe the number of interdisciplinary tumor center diagnoses (IDT) in comparison with diagnoses upon referral (ED) and radiologists? diagnoses (RD). Materials and Methods: We retrospectively reviewed 413 patients with 272 BBT and 141 TLL, classified either histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…9,19,20 As with solitary osteochondromas, the same clinicopathologic features are used to evaluate patients for possible malignant transformation (Table 1). Studies have shown that there is significant interobserver variability in the histologic diagnosis of cartilaginous tumors, 21 especially grade 1 chondrosarcoma, in patients with MHE. A multidisciplinary approach to the management of these patients with clinical and radiologic correlation is recommended, especially in cases in which malignant transformation is suspected.…”
Section: Mhe (Osteochondromatosis)mentioning
confidence: 99%
“…9,19,20 As with solitary osteochondromas, the same clinicopathologic features are used to evaluate patients for possible malignant transformation (Table 1). Studies have shown that there is significant interobserver variability in the histologic diagnosis of cartilaginous tumors, 21 especially grade 1 chondrosarcoma, in patients with MHE. A multidisciplinary approach to the management of these patients with clinical and radiologic correlation is recommended, especially in cases in which malignant transformation is suspected.…”
Section: Mhe (Osteochondromatosis)mentioning
confidence: 99%
“…To distinguish enchondroma from ACT on conventional radiographs and MRI is often difficult, especially when the lesion is located in the long tubular bones [6][7][8][9][10][11][12]. This may result in significant overtreatment of benign lesions in case of enchondroma being diagnosed as ACT.…”
Section: Introductionmentioning
confidence: 99%
“…PAX3-NCOA2 Embryonal Rhabdomyosarcoma [145,148] Loss of heterozygosity on 11p15. 5 Imprinting defects in IGF2, H19, and p57 kip2 Leiomyosarcoma [149,150] Generally complex karyotypes with numerous gains and losses…”
Section: Pax3-foxo1 Pax7-foxo1 Pax3-ncoa1mentioning
confidence: 99%
“…While some of the more common bone lesions, such as osteochondroma, pose little problem for diagnosis, the less commonly occurring benign and malignant lesions can often lead to diagnostic difficulties. The histopathologic diagnosis of bone tumors is fraught with difficulty due to the histomorphologic overlap between many different types of tumors, including overlap between reactive, benign, and malignant lesions [4][5] . In addition, the diagnosis of bone lesions is heavily reliant on correlation with imaging characteristics to be able to localize lesions to specific locations within different bones and to sometimes assist in staging [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%